Recombinant protein EBI3 attenuates Clonorchis sinensis-induced liver fibrosis by inhibiting hepatic stellate cell activation in mice - Lei Zhao; Jia Li; Gang Mo; Deping Cao; Chun Li; Guoyang Huang; Liping Jiang; Gen Chen; Hongbing Yao; Xiaohong Peng (Parasites & Vectors, 2023)
Abstract Background Chronic infection with Clonorchis sinensis can cause hepatobiliary fibrosis and even lead to hepatobiliary carcinoma. Epstein-Barr virus-induced gene 3 protein (EBI3) is a subunit of interleukin 35, which can regulate inflammatory response and the occurrence of fibrotic diseases. Previous studies have reported that the expression of EBI3 in the serum of patients with liver cirrhosis is reduced. The present study aims to investigate the biological effects of EBI3 on liver fibrosis caused by C. sinensis and the underlying molecular mechanisms. Methods We first established a mouse model of liver fibrosis induced by C. sinensis infection and then measured the serum expression of EBI3 during the inflammatory and fibrotic phase. GO (Gene Ontology) and KEGG (Kyoto Encyclopedia of Genes and Genomes) pathway analyses were performed to investigate the potential role of EBI3 in liver fibrosis by regulating the extracellular matrix structural constituent and collagen catabolic process. Recombinant protein EBI3 (rEBI3) was added to hepatic stellate cells (HSCs) in vitro with C. sinensis antigen to explore its function. Finally, the therapeutic effect of rEBI3 was verified by intravenous injection into C. sinensis-infected mice. Results The results showed that the serum expression of EBI3 increased in the inflammatory response phase but decreased in the fibrotic phase. The excretory-secretory products of C. sinensis (Cs.ESP) were able to stimulate HSC activation, while rEBI3 reduced the activation of HSCs induced by Cs.ESP. Also, the protein expression of gp130 and downstream protein expressions of JAK1, p-JAK1, STAT3 and p-STAT3 in HSCs were increased after rEBI3 incubation. Finally, intravenously injected rEBI3 inhibited hepatic epithelial-mesenchymal transition in C. sinensis-infected mice by inhibiting HSC activation and reducing liver injury. Conclusion This study confirms that rEBI3 can attenuate C. sinensis-induced liver fibrosis by inhibiting HSC activation and may be one of the potential treatments for liver fibrosis. Graphical Abstract